2012
DOI: 10.1103/physrevlett.109.075502
|View full text |Cite
|
Sign up to set email alerts
|

Planar Defect Nucleation and Annihilation Mechanisms in Nanocontact Plasticity of Metal Surfaces

Abstract: The incipient contact plasticity of metallic surfaces involves nucleation of crystalline defects. The present molecular dynamics simulations and nanoindentation experiments demonstrate that the current notion of nanocontact plasticity in fcc metals does not apply to high-strength bcc metals. We show that nanocontact plasticity in Ta-a model bcc metal-is triggered by thermal and loading-rate dependent (dynamic) nucleation of planar defects such as twins and unique {011} stacking fault bands. Nucleation of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 21 publications
10
44
0
Order By: Relevance
“…In a previous publication, a By comparing the location of the nucleated defects in (001) and (011) indentations, one can establish a clear correlation between the locations of the maximum shear stresses for the most critical {011} <0-11> and {112} <11-1> slip systems and those where SF and twins nucleate, respectively [10]. This shows that defect nucleation is indeed driven by shear.…”
Section: Critical Stresses For Defect Nucleationmentioning
confidence: 71%
See 3 more Smart Citations
“…In a previous publication, a By comparing the location of the nucleated defects in (001) and (011) indentations, one can establish a clear correlation between the locations of the maximum shear stresses for the most critical {011} <0-11> and {112} <11-1> slip systems and those where SF and twins nucleate, respectively [10]. This shows that defect nucleation is indeed driven by shear.…”
Section: Critical Stresses For Defect Nucleationmentioning
confidence: 71%
“…Surprisingly, all activation volumes vary from around 0.9 b 3 for (111) to 0.2 b 3 for (110) and (100), and were found to be almost independent of temperature and strain rate. These values are significantly lower than the 10 b 3 measured by Sato et al revealed the highly compressive stresses encountered in indentation are creating shear strains that can only be accommodated by other mechanisms such as the SFs and twins [10]. As a consequence the activation volume determined by indentation in a BCCmaterial cannot be compared to the values obtained from classical strain-rate jump tests as it describes a very specific and complex deformation scenario.…”
Section: Experimentally Measured Instrumented Indentation Responsementioning
confidence: 80%
See 2 more Smart Citations
“…Upon indentation on a (111) surface loop generation was associated with shear stresses in their atomistic indenter. Considering tantalum as a model bcc material, Alcalá and co-workers [31] have shown that nanocontact plasticity occurs by the nucleation and propagation of twin and stacking fault bands driven by a combination of shear stresses and pressure. They suggested that dislocations appear after a thermally assisted twin annihilation and mentioned that this mechanism is common to other bcc metals.…”
Section: Bcc Metalsmentioning
confidence: 99%